Konversi Bank Riau Kepri Menjadi Bank Syariah dalam Perekonomian Masyarakat dan Umat Islam di Propinsi Riau - Nurhadi Nurhadi (ISLAMIKA, 2020)
Riau public awareness of a usury-free bank has shown the positive conversion of Riau BUMD Bank Riau Riau Islands into Sharia-based Banking. Riau Kepr Bank can be converted into an Islamic bank by not breaking the existing rules, just the process and mechanism that must be followed in accordance with the procedures and rules set by the Financial Services Authority. Bank Riau Kepri if converted will become a Sharia Bank, has the opportunity to become one of the 10 largest Islamic banks in Indonesia if analyzed from the side of Riau Riau Regional BUMD assets, but still survive in conventional banks, then only in the order of 80 of the 118 banks in Indonesia, clearly it will be increasingly difficult to compete amid the ASEAN economic market and the onslaught of global banks scrambling to enter the Indonesian market. Bumi Lancang Kuning Melayu Riau and Kepri are synonymous with Islam, even though they have lived in neighboring tribes for a long time, but the law that has always been used long ago is Islamic law based on the Book of Allah and the Sunnah of the Prophet and all components of society can live peacefully and peacefully. Bank Riau Kepri was converted into a sharia bank so it would eliminate the doubt (hesitation) in the hearts of employees working in conventional banks especially with the existence of the MUI Fatwa No. 1 of 2004 stating bank interest included Haram and Riba.